New specimens of the early Eocene frigatebird Limnofregata (Pelecaniformes: Fregatidae), with the description of a new species - Olson, Storrs L.; Matsuoka, Hiroshige (Zootaxa, 2005)
Four additional specimens from the Green River Formation of Wyoming are referred to the Eocene frigatebird Limnofregata azygosternon Olson, originally described from a nearly complete skeleton and two partial paratypes. Two skulls with mandibles and a partial postcranial skeleton are described as a new species, Limnofregata hasegawai, characterized by much larger size and a proportionately longer bill. One of the referred specimens of L. azygosternon is from Eocene Lake Gosiute, whereas all of the other specimens of Limnofregata are from Fossil Lake. The species of Limnofregata would have taken advantage of frequent periodic dieoffs of fish in the Green River lakes. Geological and climatic factors that may have influenced the paleoecology, distribution, and size variation in frigatebirds in the Cenozoic are reviewed.